CHARACTERISTICS OF PEDIATRIC BURNS AND INITIAL FIRST AID AMONG CHILDREN TREATED AT SAINT PAUL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe burn characteristics and initial first-aid practices among pediatric burn patients treated at the Burn Department of Saint Paul General Hospital, Hanoi, from June to August 2025.Methods: A prospective descriptive cross-sectional study included 50 pediatric burn patients aged 0–15 years. Epidemiological characteristics, burn injuries, and first aid at the injury scene were summarized using frequencies and percentages.Results: Children aged 1–3 years accounted for 42%, and boys for 64%. Scalds accounted for 92%, and all recorded injuries occurred at home. Lower limbs were the most frequent site (28.9% of recorded sites). Total burn surface area was available for 48/50 children: 24/48 (50.0%) had
Keywords: pediatric burns; burn first aid; scald; Saint Paul General Hospital.